Phytoplankton standing crop and its diversity in the Buragauranga River estuary in relation to chemical environment (Bangladesh Journal of Botany, 2011)
Chemical and biological features of Buragauranga river estuary stretching about eight kilometers beside Rangabali of Galachipa Upozilla, Patuakhali district, Bangladesh showed that the water of the estuary was moderately alkaline (pH 7.8 - 8.21). Conductivity had moderate to very strong and perfect significant correlations (at 5% level) with the chemical variables. Magnesium was found to have very strong relationship with different fractions of hardness whereas Ca had moderate correlation. The phytoplankton community was represented by 10 genera belonging to Chlorophyceae, Euglenophyceae and Bacilariophyceae. Bacillariophyceae was the dominant algal class (8 genera, 80%). Trachelomonas sp. of Euglenophyceae was present in all the 12 sampling units of 3 locations indicating its dominancy and capacity to tolerate habitat fluctuations. Location 2 showed higher generic diversity than the other two locations. Principal component analysis showed that Trachelomonas sp. has negative significant correlation with principal component one i.e. Mg, K, conductivity, dissolved oxygen, biological oxygen demand and salinity have negative effect on the distribution of Trachelomonas sp. whereas these variables have positive effects on Coscinodiscus sp. Key words: Phytoplankton standing crop; Diversity; Estuary; Chemical environment; Bangladesh DOI: 10.3329/bjb.v39i2.7300 Bangladesh J. Bot. 39(2): 143-151, 2010 (December)